Synthesis, Crystal Structure, and DNA-Binding Studies of a Nickel(II) Complex with the Bis(2-benzimidazolymethyl)amine Ligand - Huilu Wu; Tao Sun; Ke Li; Bin Liu; Fan Kou; Fei Jia; Jingkun Yuan; Ying Bai (Bioinorganic Chemistry and Applications)
A V-shaped ligand Bis(2-benzimidazolymethyl)amine (bba) and its nickel(II) picrate (pic) complex, with composition [Ni(bba)2](pic)2⋅3MeOH, have been synthesized and characterized on the basis of elemental analyses, molar conductivities, IR spectra, and UV/vis measurements. In the complex, the Ni(II) ion is six-coordinated with a N2O4 ligand set, resulting in a distorted octahedron coordination geometry. In addition, the DNA-binding properties of the Ni(II) complex have been investigated by electronic absorption, fluorescence, and viscosity measurements. The experimental results suggest that the nickel(II) complex binds to DNA by partial intercalation binding mode.